Determination of some nutritional value and organoleptic properties in fruity teas - Sohrabvandi, Sara; Oroognia, Peyman; Mortazavian, Amir Mohammad; Khoshfarjham, Mehraein; Ahmadi, Nayebali (Archives of Advances in Biosciences, 2013)
Fruity teas are popular due to variety in sensory properties as well as their nutritional and therapeutical characteristics. Recently, the worldwide researches related to fruity teas have been considerably developed. In this work, effects of fruit type (apple, quince and pear) and brewing time (10 or 20 min) on some nutritional properties (Mg, Fe and Ca contents, sugars and protein percent) as well as on the sensory attributes of final products were investigated. No chemical preservative, flavoring gents and colorants were added for preparation of the samples. At the end of 10 min brewing, the highest extraction rates of Mg and protein, Fe and sugars, and Ca were observed for pear, apple, and quince, respectively. At the end of 20 min brewing, the greatest extraction rates of Mg and protein, sugars, and Ca were related to the pear, apple, and quince, respectively. Increasing the time of brewing up to 10 min although did not noticeably affect the extraction rate of nutrients from dried fruits (especially for protein content), significantly influence the sensory characteristics (flavor and color) of final products; so that those prepared by 20 min brewing had higher acceptability. Among the fruity teas produced by 20 min brewing, apple had the best sensory acceptability from flavor and color points of view. After that, pear tea from taste and quince tea from color standpoints were realized as the best samples.